Cross-sectional serosurvey of Leptospira species among slaughter pigs, goats, and sheep in Uganda - Alinaitwe, Lordrick; Aturinda, C.J.; Lubega, A.; Kivali, Velma; Bugeza, James; Wainaina, M.; Richter, M.H.; Hoona, J.J.; Roesel, Kristina; Mayer-Scholl, A.; Cook, Elizabeth A.J.; Kankya, C.; et al. (2024)
Introduction Leptospira are a group of bacteria, including pathogenic types that cause leptospirosis. In Uganda, Leptospira exposure has been reported in humans, with domesticated animals being speculated as the source. However, comparable evidence of Leptospira prevalence and circulating serovars/serogroups in animals is only documented for cattle, and dogs. Our study determined Leptospira seroprevalence, associated risk factors and serogroups circulating among slaughtered pigs, goats, and sheep in Uganda.